RESISTANCE OF SELECTED GERMPLASMS OF BENGAL GRAM AGAINST CALLOSOBRUCHUS CHINENSIS L. (COLEOPTERA : BRUCHIDAE) - SHARMA, MUKESH K.; DWIVEDI, S. C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1996)
Nine different varieties of Bengal gram were evaluated for their relative susceptibility against the pulse beetle, Callosobruchus chinensis. Ovipositional preference, growth and damage caused were the main criteriaofevaluation. It was found that two of the selected varieties i.e. C-235 and Katader-1705851 were hardy enough to resist any infestation by the beetle.